IMPLEMENTASI KEBIJAKAN PEMBELAJARAN PROGRAM PAKET C SELAMA MASA PANDEMI COVID-19 (STUDI DI PUSAT KEGIATAN BELAJAR MASYARAKAT HARAPAN BANGSA 1 KOTA BANDAR LAMPUNG) - Eko Purnomo; Muhammad Oktaviannur (Universitas Bandar Lampung (UBL), 2021)
The problems in this study are: (1) how is the implementation of the package c program learning policy during the covid-19 pandemic period at pkmb harapan bangsa 1 bandar lampung city? (2) what are the aspects that hinder and support the implementation of the package c program learning policy during the covid-19 pandemic period at pkmb harapan bangsa 1 bandar lampung cityThe research method which according to the researcher is in accordance with this research method is to use a qualitative type of research with a descriptive analysis method. the use of this method is to describe and study qualitatively, how the implementation of the package c program learning policy during the covid-19 pandemic period at the hope community learning activity center nation 1 city of bandar lampung. all data were obtained directly from informants in the field using interviews and observations.The results showed that the implementation of the package c program learning policy during the covid-19 pandemic at the harapan bangsa 1 community learning activity center, bandar lampung city, had been running. this is in accordance with the results of the study showing that the policy has been running, but it has not been optimal, this occurs due to a lack of socialization, so that information about the implementation of the package c learning policy during this pandemic is ineffective, and the lack of supporting infrastructure facilities for learning with online methods are very effective. minimal budget so that teaching and learning activities at the community learning activity center (pkmb) have not been maximized.The implementation of the learning policy of the package c program shows that online learning has not run optimally because of several obstacles such as the economic level is relatively weak, signal constraints, quota costs so that the implementation of the package c learning program at the harapan bangsa community learning activity center in bandar lampung city which has not been fully implemented. as planned due to limited human resources who master information technology (it), as well as the lack of learning support facilities and still in dire need of attention and assistance from the government